Guilt : anxiety reaction of parents in having an intellectually handicapped child : an independent project presented in partial fulfilment of the requirements for the degree of Master of Arts in Applied Psychology [at] Massey University. - Jolly, Audrey Brunette (Massey University, 1977)
Chronic Guilt: Parents emotional attitude response to having a mentally defective child. The aim of this project is two-fold (1) To propose that most parents who have a mentally defective child suffer from a pervasive psychological reaction, chronic guilt, and that it is not always recognized by the professional personnel – physicians, psychologists, and social workers, who attempt to help them (2) To suggest some of the implications of the phenomenon of chronic guilt for parent counselling processes. Chronic guilt is a complex emotional attitude of long term duration and generally involving emotional conflict, grief, fear, love, anxiety, anger, hatred, protection, sympathy and defensive elements, and arising out of real or imagined contravention of moral and social standards in act or thought. Most, if not all, of these parents suffer from chronic guilt throughout their lives regardless of whether the child is kept at home or 'put away'. The intensity of this guilt varies from time to time for the same person, from situation to situation, and from one family to another. chronic guilt may be more intense for one parent than the other in the same family. Many factors such as parents personality, ethnic origin, religion and social class can influence the intensity of this feeling. Although chronic guilt may be felt by some parents of minimally retarded children, the phenomenon is almost universal among parents of severely or moderately retarded children, that is those children who would be regarded as retarded in any society or group. The reality faced by the parents of severely retarded children is such as to justify the chronic guilt. When a parent is asked to accept mental deficiency it is not clear just what he is asked to do. The stress placed on acceptance may suggest to the parent that he is expected to see his or her child from the point of view of the professional. This expectancy can make the parent both resentful and resistant. The first part of this study reviews some of the important literature published during the past twenty years, and suggests that trait factor analysis could be a basis for the chronic guilt syndrome. The second part of the study is a field investigation of Wolfensberger's theory that guilt can be a positive attribute. From a small New Zealand sample of parents of handicapped children, who were referred or visited over one month (Kimberley Hospital) and asked to complete the 16 PF, four trait factors were extracted to support the contention and underline the complexity of the chronic guilt.
Keywords: Guilt; Children with mental disabilities